2020
DOI: 10.3390/catal10111325
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Solvothermal Synthesis of Fe3O4/CeO2 Nanocomposites and Their Catalytic Activity in the Imine Formation from Benzyl Alcohol and Aniline

Abstract: Fe3O4/CeO2 nanocomposites were synthetized by coating magnetite seeds of different morphologies (hexagonal, spheroidal, quasi-spherical) with ceria, in ethylene glycol as solvothermal solvent. The synthesis was performed in the presence of microwave irradiation aiming to overcome the common disadvantages proper of the classic solvothermal/hydrothermal procedure. The obtained nanocomposites were calcined at the optimum temperature of 550 °C. The structure of the new nanomaterials was carefully investigated by I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…[49] In this case, the presence of organic residues might hamper the migration of the substrates towards the catalytic centres, thus lowering the final yields, as already observed, for example, for ceria-based nanocomposites. [50] Since the nanometric hematite in Hem_400_Air turned out to be an efficient and selective catalyst for the hydrogenation of nitrobenzene and p-bromonitrobenzene, the question arises whether ore hematite is also an active catalyst for this reaction. Thus, we tested natural micrometric hematite (Nat_Hem) in the hydrogenation of p-bromonitrobenzene.…”
Section: Catalytic Testsmentioning
confidence: 99%
“…[49] In this case, the presence of organic residues might hamper the migration of the substrates towards the catalytic centres, thus lowering the final yields, as already observed, for example, for ceria-based nanocomposites. [50] Since the nanometric hematite in Hem_400_Air turned out to be an efficient and selective catalyst for the hydrogenation of nitrobenzene and p-bromonitrobenzene, the question arises whether ore hematite is also an active catalyst for this reaction. Thus, we tested natural micrometric hematite (Nat_Hem) in the hydrogenation of p-bromonitrobenzene.…”
Section: Catalytic Testsmentioning
confidence: 99%
“…After the incorporation of the green chemistry principles into the synthetic chemistry modus operandi, following the works of Anastas & Warner (1998), the above mentioned syntheses were improved further and rendered more eco-friendly through the use of heterogeneous catalysts such as: sulfated-TiO 2 , montmorillonite K-10 clay, sulfated nano-ordered silica and zeolites (Kumar et al, 2016;Atanassova et al, 2011;Naimi-Jamal, Ali & Dekamin, 2013;Amrutham et al, 2017). Further recently developed sustainable methodologies have been reported using irradiation techniques (Rizzuti et al, 2020). Moreover the addition of dehydrating agents such as phosphorous-pentoxide-silica have also been shown to drive the reaction to completion by removing the condensation product, ergo water (Naeimi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…CeO 2 is a new promising catalyst for imine synthesis, which can overcome the problems caused by traditional acid/base catalysts ( Tamura and Tomishige, 2015 ) and bring a lot of advantages, such as mild synthesis conditions and fast separation. Many research studies have focused on CeO 2 application in imine synthesis ( Geng et al, 2016 ; Long et al, 2019a ; Long et al, 2019b ; Cao et al, 2020 ; Rizzuti et al, 2020 ; Tamura and Tomishige, 2020 ), and it has been reported that CeO 2 morphologies can greatly influence the catalytic activity for imine synthesis ( Zhang et al, 2017 ; Yang et al, 2018 ; Zhang et al, 2018 ; Yang et al, 2020a ; Yang et al, 2020b ), which have a close relationship with the CeO 2 specific surface area and Ce 3+ defects.…”
Section: Introductionmentioning
confidence: 99%